1986
DOI: 10.1203/00006450-198606000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Response Audiometry in Congenitally Hypothyroid Children Under Early Replacement Therapy

Abstract: ABSTRACT. Using auditory brainstem response audiometry, we evaluated 34 congenital hypothyroidism children under thyroid hormone therapy and 24 age-and sexmatched controls between 5 and 12 yr of age. Two main auditory brainstem response abnormalities were encountered: first, prolonged wave I latencies, secondary to a peripheral impairment, were found in seven congenital hypothyroidism children (20%): three of these showed signs of serious otitis media, unilaterally in two and bilaterally in the other, at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 1 publication
0
12
0
2
Order By: Relevance
“…Hearing impairment has been associated with (53,54,55,56,57) and others reporting no such impairment (54,58). One study investigated 12 older patients, at the age of 20 years, and suggested that auditory processing abnormalities persisted in these patients (59).…”
Section: Neurosensory Developmentmentioning
confidence: 99%
“…Hearing impairment has been associated with (53,54,55,56,57) and others reporting no such impairment (54,58). One study investigated 12 older patients, at the age of 20 years, and suggested that auditory processing abnormalities persisted in these patients (59).…”
Section: Neurosensory Developmentmentioning
confidence: 99%
“…42,43 Evidence from 4-year longitudinal studies of language and auditory processing skills in young children with congenital hypothyroidism shows essentially no difference in the expressive language skills between 7-yearolds with and without hearing impairments, 17 although the cohorts with hearing impairments continued to exhibit receptive language and reading deficits on serial assessment. 17 In a cross-cultural prospective study of nonverbal short-term memory span and pictorial serial ARCH INTERN MED/ VOL 158, JULY 13,1998position memory in teenagers from Papua New Guinea (most of whom had an iodine deficiency and mothers who had received supplementary iodine during pregnancy), 44 measured levels of total maternal thyroxine were not significantly associated with simple short-term memory span when the cohorts were 14 to 15 years old. However, on testing 2 year later, levels of total maternal thyroxine were significantly associated with more complex reverse order memory span operations and moderately associated (r = 0.39) with serial position memory.…”
Section: Follow-up Studies In Congenital Hypothyroidismmentioning
confidence: 99%
“…These prolonged PI latencies are in accordance with the elevated ABR thresholds we previously measured, 36 since these physiological markers are associated with peripheral hearing loss. 72 In contrast, the lack of effect on BTT indicated that mild prenatal IDA had no effect on neural transmission time along the brainstem (central) portion of the auditory pathway. We also observed IDA effects on ABR amplitudes in that females from IDA siblings were hyper-responsive to various stimulus intensities.…”
Section: Discussionmentioning
confidence: 99%